Hexagonally arranged arrays of urchin-like Ag-nanoparticle decorated ZnO-nanorods grafted on PAN-nanopillars as surface-enhanced Raman scattering substrates. Issue 25 (6th June 2018) - Tang, Fang; Zhang, Meizhu; Li, Zhongbo; Du, Zhaofang; Chen, Bensong; He, Xuan; Zhao, Siyu
Abstract : Large-scale flexible films with one side consisting of ordered Ag-NPs@ZnO-nanorods/PAN-nanopillar arrays were used as recyclable SERS substrates. Abstract : Surface-enhanced Raman scattering (SERS) is one of the most promising methods in detecting trace amounts of molecules owing to its high sensitivity, fast response, and high molecular specificity. One of the key issues for SERS applications is to fabricate highly sensitive and homogeneous SERS substrates. Here, we present a template-assisted synthetic approach to fabricate urchin-like Ag-nanoparticle (Ag-NP) decorated ZnO-nanorods grafted on hexagonally ordered polyacrylonitrile (PAN) nanopillar arrays as flexible and reliable surface-enhanced Raman scattering (SERS) substrates, which are achieved by a combined process of molding highly ordered PAN-nanopillar array films, electrochemical depositing ZnO nanorods onto molded PAN nanopillar arrays, then sputtering Ag-NPs onto the surface of ZnO nanorods. The resultant hetero-hierarchical nanostructure exhibits not only much stronger SERS activity but also uniform SERS signals over the whole arrays based on the high density of nanogaps (hot spots) between the neighboring Ag-NPs on both the same ZnO-nanorods and adjacent ZnO-nanorods and the highly ordered PAN-nanopillar arrays. Using the Ag-NP assembled ZnO-nanorod arrays as SERS-substrates, not only 10 −13 M Rhodamine 6G has been identified, but also 10 −8 M parathion-methyl has been recognized, showing great potential in detection of trace organic pollutants in the environment. Furthermore, the Ag-NPs@ZnO-nanorods could achieve self-cleaning and reactivation of SERS-activity by simple UV light irradiation and retain stable SERS sensitivity even after five cycles, demonstrating the high reusability of the hybrid substrates.